Pemberian Kompos Bahan Sampah Serat Bromelain Yang Diinduksi Inokulum Fungi Selulolitik Aspergillus sp. Pada Pertumbuhan Vegetatif Cabai (Capsicum annuum L.) - Fadila Raisyadikara; Bambang Irawan; Salman Farisi; Yulianty Yulianty (Jurnal Biologi Papua, 2022)
The purpose of this research is to understand the effect and the best dossage of bromelain wastes solid compost for vegetative growth of chilli plants. Accumulation of pineapple wastes made by the large pineapple plantation area. The litter of pineapple bromelain enzyme (bromelain wastes) still containing organic matter that could composted for plant nutrition. The composting of it can be accelerated by induction inoculum of cellulotic Aspergillus sp. fungus. The research used Completely Randomized Design method with seven treatment and three replications. The treatment used two different type of compost. The composition of compost A type is:  0,5 kg bromelain + 0,5 kg leaves litter + 0,5 kg livestock wastes + inoculum 1%. The composition of compost B type is:  1 kg bromelain + 0,5 kg livestock wastes + inoculum 1%. The treatment conducted P0:  5 kg soil (control). P1:  5 kg soil + 1,4% A type compost. P2: 5 kg soil + 1,7% A type compost. P3: 5 kg soil + 2% A type compost. P4: 5 kg soil + 1,4% B type compost. P5: 5 kg soil + 1,7 % B type compost. P6: 5 kg soil + 2% B type compost. Variance analyzed of obtained data were using ANOVA and tested using the Least Significant Difference Test (LSD) method. Parameter of this study are number of leaves and chlorophyll content. The results showed that the application of P6: 2% dossage B type compost from bromelain solid compost could optimized the vegetative growth of chili plants (Capsicum annuum L.). Key words: Aspergillus sp.; bromelain; chili; compost.